2021
DOI: 10.3389/fpos.2021.630133
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging COVID-19 Vaccine Uptake Through Effective Health Communication

Abstract: Context: Overcoming the COVID-19 pandemic will require most Americans to vaccinate against the virus. Unfortunately, previous research suggests that many Americans plan to refuse a vaccine; thereby jeopardizing collective immunity. We investigate the effectiveness of three different health communication frames hypothesized to increase vaccine intention; emphasizing either 1) personal health risks, 2) economic costs, or 3) collective public health consequences of not vaccinating.Methods: In a large (N = 7,064) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
126
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 35 publications
12
126
0
2
Order By: Relevance
“…A study that was conducted in the United States about the uptake of the Human Papilloma Virus (HPV) has shown that individuals' engagement with anti-vaccine messages on social media has a negative impact on their intentions to get vaccinated [58]. Literature on health communication has shown that emphasizing the benefits of partaking in health behavior rather than portraying the harms of refusing to take the health behavior and focusing on the immediate and personalized benefits rather than distant societal benefits are more effective in delivering health promotion messages [59].…”
Section: Discussionmentioning
confidence: 99%
“…A study that was conducted in the United States about the uptake of the Human Papilloma Virus (HPV) has shown that individuals' engagement with anti-vaccine messages on social media has a negative impact on their intentions to get vaccinated [58]. Literature on health communication has shown that emphasizing the benefits of partaking in health behavior rather than portraying the harms of refusing to take the health behavior and focusing on the immediate and personalized benefits rather than distant societal benefits are more effective in delivering health promotion messages [59].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tailoring messages to different hesitancy drivers is a guiding strategic communication principle for all health communication. A recent experimental survey argued that framing the issue as a matter of personal and collective health risk had a positive effect (Motta et al, 2021). The herd community argument has been shown to reduce vaccine hesitancy in other populations too (Schwarzinger et al, 2021).…”
Section: Consequences For Content Strategiesmentioning
confidence: 99%
“…Previous research on hesitancy towards other vaccines (Betsch et al, 2017;Betsch & Böhm, 2018) and preliminary studies on COVID-19 vaccine intentions (Motta et al, 2021;Williams et al, 2020) suggest that this framing may be effective in increasing vaccine acceptance. As more evidence of the effect of vaccination on transmission becomes available, researchers should investigate the how communicating such evidence impacts vaccine attitudes and intentions.…”
Section: Discussionmentioning
confidence: 99%
“…However, no control group was included in the study-leaving it unclear which interventions shifted beliefs relative to a baseline. In another messaging experiment, Motta et al (2021) report that messages framed to emphasise the collective benefits of vaccination or the risks of not vaccinating increased participants' vaccine intentions-however the presence or absence of information about the rigorousness of clinical trials had no impact on intentions. Palm et al (2021) find that messages highlighting vaccine efficacy and safety had a marginally significant effect on vaccine intentions relative to a control group, while an opposite message claiming planned vaccines were neither effective nor safe had no main effect on intentions.…”
Section: The Effect Of Covid-19 Vaccine Communications On Intentionsmentioning
confidence: 98%